COVID-19 Pandemic and the Moral Values in Christianity and Islam - Bekhouche, Abdelkader; Rahmatullah, Zainab (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
Religious beliefs have always been the stimulating motives for human behavior. Man’s need for religion is not specified to a certain era in time. Rather, it extends over all the times and eras; as a man still invokes religion in the face of ever-rising challenges. One of the most serious of these challenges that humans constantly face is epidemics and diseases. There is no doubt that the two religions, Christianity and Islam, enjoy a high moral heritage. This study aimed to demonstrate the impact of the COVID-19 pandemic on societies, and the importance of Islamic and Christian values in dealing with the pandemic in different societies of the world, by reviewing and analyzing the discourse of religious scholars and priests, and through the sacred texts of the two religions, in addition to reviewing the studies that discussed the pandemic and religious values. The study explained how the Islamic and Christian religious discourses employed morals to confront the pandemic, as they supported and emphasized the precautionary measures, such as home quarantine and social distancing. They also stressed the need for unity, cooperation and solidarity to confront the pandemic in order to preserve the security of societies.